STUDI DESKRIPTIF VOLUME URIN 24 JAM PADA IBU HAMIL - Kartika Putri Yuwono; Wahyu Hidayati (Jurnal Keperawatan Diponegoro, 2012)
Urinary elimination is one of the body's metabolic process that aims to remove the residue from the body. Many factors influence the changes in urine volume and quality as well as the client's ability to urinate. Changes in urinary elimination may also occur in women who are pregnant. The purpose of this study to describe the picture of a 24-hour urine volume in pregnant women in the work area Mangkang health center. This type of quantitative research using descriptive method approach. Observation data collection sheet. Number of respondents 51 people with accidental sampling technique. Results of research showed that respondents have urine volume> 1600 mL in trimester 1 of 4 people (7.8%), second trimester there are 18 people (35.3%), third trimester there are 12 people (23.5%) and respondents with urine volume> 1500 mL in trimester 1 of 4 people (7.8%), second trimester as many as 8 people (15.7%), trimester 3 of 3 people (5.9%). Respondents who had urine volume range 1500 - 1600 ml in trimester 1 of 1 people (2.0%) and second trimester as many as 1 person (2.0%). There are 36 respondents experienced an increase in urine volume of normal adult urine volume of about 1500-1600 ml. Fluid intake in the mother during pregnancy should be increased because of increased fluid requirements during pregnancy